2013
DOI: 10.1111/cen.12134
|View full text |Cite
|
Sign up to set email alerts
|

Serum FGF21 concentration is associated with hypertriglyceridaemia, hyperinsulinaemia and pericardial fat accumulation, independently of obesity, but not with current coronary artery status

Abstract: Serum FGF21 concentrations were significantly associated with lipid profiles, insulin resistance, pericardial fat volume and MS, independently of obesity, but not with overt CAD or diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
61
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 42 publications
(62 reference statements)
12
61
1
Order By: Relevance
“…Unfortunately, the increased endogenous FGF21 level was not sufficient when the exogenous FGF21 administration comes into play a role for therapeutic strategy. The FGF21 resistance was also observed in clinical reports where serum FGF21 level was significantly increased in non-NAFLD (Shen et al 2013), coronary heart disease (Lin et al 2010, Shen et al 2013, metabolic syndrome (Lee et al 2014), andT2DM (Lenart-Lipinska et al 2013). This condition is similar to what has been observed in subjects under 'insulin resistance' condition in which the impairment of insulin receptor and signaling cascades was found with increased plasma insulin level (Pratchayasakul et al 2011, Pipatpiboon et al 2012.…”
Section: Clinical Evidence Of the Association Between Fgf21 And Cardimentioning
confidence: 64%
See 1 more Smart Citation
“…Unfortunately, the increased endogenous FGF21 level was not sufficient when the exogenous FGF21 administration comes into play a role for therapeutic strategy. The FGF21 resistance was also observed in clinical reports where serum FGF21 level was significantly increased in non-NAFLD (Shen et al 2013), coronary heart disease (Lin et al 2010, Shen et al 2013, metabolic syndrome (Lee et al 2014), andT2DM (Lenart-Lipinska et al 2013). This condition is similar to what has been observed in subjects under 'insulin resistance' condition in which the impairment of insulin receptor and signaling cascades was found with increased plasma insulin level (Pratchayasakul et al 2011, Pipatpiboon et al 2012.…”
Section: Clinical Evidence Of the Association Between Fgf21 And Cardimentioning
confidence: 64%
“…Moreover, epicardial fat and muscular FGF21 mRNA expression increased after surgery has reacted positively with blood glucose levels at the end of surgery (Kotulak et al 2011) indicating that FGF21 mRNA expression and serum FGF21 levels regulated glucose homeostasis, increased the insulin sensitivity and attenuated the inflammatory process. In a cross sectional study of 189 patients who underwent cardiac multidetector coronary computed tomography, it was found that serum FGF21 levels were associated with an adverse lipid profile and pericardial fat volume only in metabolic syndrome patients (Lee et al 2014). Interestingly, cardiac tissue FGF21 mRNA and antioxidant genes (UCP3 and Sod2) are upregulated in six failing human hearts which may be mechanisms to preserve myocardial function in cases of heart failure (Planavila et al 2014).…”
Section: Clinical Evidence Of the Association Between Fgf21 And Cardimentioning
confidence: 99%
“…In a study involving 100 Chinese subjects, with 38% of them having T2DM, serum FGF21 levels were independently associated with the presence of acute myocardial infarction and were significantly higher in those who developed reinfarction within 30 days 15. However, conflicting results were also reported from a few studies, which showed a lack of significant association after adjusting for body mass index and glycemic status 16, 17. Given that circulating FGF21 levels were higher in T2DM,6, 9 and most cross‐sectional studies consisted of relatively small sample size and therefore a limited number of subjects with T2DM, the association of serum FGF21 with CHD in T2DM could only be, at most, speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the association of circulating FGF21 with CHD in T2DM has not been clearly defined. In cross‐sectional studies, conflicting results were reported regarding circulating FGF21 levels in subjects with CHD, with an association of raised FGF21 levels with CHD reported in some studies,13, 14, 15 but not in others 16, 17. The association of circulating FGF21 with CHD in T2DM, especially among those without known cardiovascular disease (CVD), remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…5,10 However, the precise nature of the association between serum FGF21 concentrations and CAD has yet to be confirmed. 4,11,12 In this study, we compared serum FGF21 concentrations in individuals with or without coronary artery narrowing, as identified by coronary angiography (CAG), and determined whether circulating FGF21 concentrations are associated with the severity of CAD.…”
Section: Introductionmentioning
confidence: 99%